Situation Report: Bulgaria, 25 November 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Bulgarian Coverage of the French Financial Crisis Rumors about Soviet Troops and Bulgarian-Yugoslav Relations New Bulgarian-Soviet Fishing Agreement Decree on Professional Orientation of Youth Comings and Goings East European Cultural Ministers Meet in Sofia Economic Delegation in Cairo Tano Tsolov to Moscow Pencho Kubadinsky Returns Home Deputy Minister of Transport in North Vietnam